La fantasia come motore del pensiero: ricordo di Antonio Rostagno (Materiali di Estetica. Terza serie, 2022)
In this short article I recall some significant episodes of my intellectual relationship to Antonio Rostagno. The double meaning of the word "phantasy" allows me to refer both to a discontinuous and paratactic musical form, deeply connected with the Romantic experience, and to Rostagno's capacity of opening unexpected perspectives on known facts. I comment upon passages of his writings, talks and letters. I conclude with a reflection on the convergent elements of Hölderlin and Schumann, a topic which belongs to our common research fields
Keywords: Musical theory; Romanticism; Hölderlin; Schumann